Widen the Circle: Translingual Poetics & Children’s Poetry in the Work of Yan Satunovsky - Morse, Ainsley (Wiener Slawistischer Almanach, 2025)
This paper addresses multi- and translingual aspects of the work of Soviet unofficial poet Yan Satunovsky. It considers biographical, professional, creative and emotional factors contributing to multilingualism in Satunovsky’s work, including his childhood in early-Soviet Ukraine, his Jewish identity, his status as an unofficial poet and his work as a translator and author of children’s poetry. Examples from children’s and adult poems elucidate the different languages Satunovsky worked in and the difference between multilingual and translingual poetics. The article concludes with a reflection on the larger significance of multi- and translingual poetry for Satunovsky and his time.